Effect of XFEM mesh density (mesh size) on stress intensity factors (K), strain gradient (dεdr) and stress corrosion cracking (SCC) growth rate. (June 2020) - Bashir, Rehmat; Xue, He; Zhang, Jianlong; Guo, Rui; Hayat, Nasir; Li, Ganbo; Bi, Yueqi
Abstract: The extended finite element method (XFEM) is now widely used for crack simulations. The researchers have performed the crack simulations using the XFEM without re-meshing. Due to recent problems of discrepancies in the experimental and computational results, the mesh density (numbers of elements/unit area) or mesh size of the XFEM is a questionable field . In this research, the effect of the XFEM mesh density (mesh size) on stress intensity factors (K), strain gradient ( d ε dr ) and stress corrosion cracking (SCC) growth rate has been investigated using the XFEM method provided by the ABAQUS . Two specimens with embedded cracks in a flat plate of Inconel-600, under the same load and environment (340 °C), are used. The embedded cracks are of different lengths with localized circles of randomly chosen radius. The stress intensity factors, K, strain gradient with respect to the propagated crack, d ε dr, and the stress corrosion cracking (SCC) growth rate are estimated. In order to check the trend, the process is repeated on three different applied loads. It has been noticed, well studied and proposed that when "local mesh size (MS)" to "embedded crack length (Le)" ratio (MS/Le) ≤ 0.0005 in two of the specimen used, the K and d ε dr become smooth and the simulated SCC crack growth results are nearest to the experimental values of the SCC crack growth rate.